IRS Reform: Politics As Usual? - Lederman, Leandra (Columbia Journal of Tax Law, 2016)
The IRS is still reeling from accusations that it “targeted” Tea Party and other non-profit organizations. Although multiple government investigations found no politically motivated behavior—only mismanagement—Congressional hearings were quite inflammatory. Congress recently followed up those hearings with a set of IRS reforms. Congress’s approach is reminiscent of the late 1990s, when highly publicized Congressional hearings regarding alleged abuses by the IRS resulted in a major IRS reform and restructuring, although the allegations subsequently were largely debunked. This Article argues that the recent allegations against the IRS also were overblown. It looks to the aftermath of the 1998 IRS reform, which included a major downturn in enforcement, for lessons for the present day. The Article concludes that Congress as a whole can do a better job of keeping politics from undermining tax administration.